The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1037/amp0000146
|View full text |Cite
|
Sign up to set email alerts
|

Risky business: Correlation and causation in longitudinal studies of skill development.

Abstract: Developmental theories often posit that changes in children's early psychological characteristics will affect much later psychological, social, and economic outcomes. However, tests of these theories frequently yield results that are consistent with plausible alternative theories that posit a much smaller causal role for earlier levels of these psychological characteristics. Our paper explores this issue with empirical tests of skill building theories, which predict that early boosts to simpler skills (e.g., n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 60 publications
8
79
0
Order By: Relevance
“…We found that projected impacts systematically over‐estimated observed impacts, replicating Bailey et al. (). Thus, given the implausibility of regularly collecting a battery of pretest controls more thorough than those included in this study, regression control does not appear to provide an effective means for projecting the future benefits of successful interventions.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…We found that projected impacts systematically over‐estimated observed impacts, replicating Bailey et al. (). Thus, given the implausibility of regularly collecting a battery of pretest controls more thorough than those included in this study, regression control does not appear to provide an effective means for projecting the future benefits of successful interventions.…”
Section: Discussionsupporting
confidence: 86%
“…The extent to which these findings generalize to other types of interventions, target skills, and age groups is not well understood. The finding that intervention effects declined to approximately 1/3 their initial size after the first year is similar to findings from prior comparisons of fadeout effects across multiple studies of academic interventions in early childhood and the early school years (Bailey et al., ; Li et al., ). It is less clear if this pattern generalizes well to interventions targeting older children.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…different measures were administered at different time points), the authors do not implement repeated measures and are therefore unable to control for the preexisting relation between symbolic and non‐symbolic processing at time one. As such, these studies do not provide strong evidence for a relation between non‐symbolic skills at time one and growth in symbolic number abilities (see Bailey, Duncan, Watts, Clements, & Sarama, ).…”
Section: Introductionmentioning
confidence: 84%